ADAPTATION OF MAINLAND CHINA ARCHITECTURAL CHARACTERISTICS ON CHINESE PERANAKAN HOUSES IN YOGYAKARTA - Thalita Kumala; Dyah Titisari Widyastuti (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2023)
This paper lists the architectural characteristics of Chinese Mainland Architecture in terms of architectural heritage conservation. Chinese residing in various countries can strongly maintain their culture, showing a distinctive architectural identity. The concept experienced adaptation to various natural and cultural contexts of countries outside their home country, the four-seasons country, Mainland China. The current situation of fast-growing construction, developments, and alteration of cultures and nature is both an opportunity and a threat to old Chinese housing. This paper aims to identify and understand architectural characteristics enabling physical conservation holistically. Research methods are in stages, the first stage being a literature review on typology and principles of Chinese architecture; the second stage is to structure and analyze the characteristic architectural findings; and the third stage is to draw conclusions from the process of interpretation, answering the research questions. A holistic literature review is needed to understand and categorize each housing based on its architectural characteristics.